The relationship between lipids level and cerebral microbleeds in patients with spontaneous intracerebral hemorrhage - Hao Feng; Xin Wang; Wenjuan Wang; Xingquan Zhao; Xingquan Zhao; Xingquan Zhao; Xingquan Zhao (Frontiers in Neurology)
BackgroundPrevious studies indicate a potential link between elevated serum lipid levels and an increased risk of cerebral microbleeds (CMBs). Since multiple CMBs can elevate the risk of future intracerebral hemorrhage (ICH), it is important to explore the relationship between lipid profiles and CMBs in ICH patients. However, data on this specific correlation in ICH populations are currently limited.MethodsThis study retrospectively enrolled 223 consecutive patients from a spontaneous ICH cohort. We collected comprehensive clinical, demographic, and laboratory data, with a focus on lipid levels and the presence of CMBs. Using a multivariate logistic regression model, we investigated the association between lipid parameters and CMB occurrence.ResultsAmong the 223 patients, 111 (49.8%) had CMBs. Univariate analysis showed that individuals without lobar CMBs tended to have higher levels of serum total cholesterol (TC), low-density lipoprotein (LDL), and non-high-density lipoprotein (Non-HDL). After adjusting for potential confounders, TC [odds ratio (OR), 0.989; 95% confidence interval (CI), 0.979–0.999; p = 0.028] and Non-HDL (OR, 0.989; 95% CI, 0.979–1.000; p = 0.043) were identified as independent predictors of lobar CMBs.ConclusionOur findings suggest an inverse correlation between TC and Non-HDL levels and the presence of lobar CMBs in ICH patients. Further prospective studies are needed to clarify the causal relationship between statin use and CMBs in ICH patients and to evaluate the prognostic significance of CMB presence and severity in statin-treated individuals.